Discrimination in the United States: Experiences of lesbian, gay, bisexual, transgender, and queer Americans - Casey, Logan S.; Reisner, Sari L.; Findling, Mary G.; Blendon, Robert J.; Benson, John M.; Sayde, Justin M.; Miller, Carolyn (Health services research, 2019)
Objective To examine reported experiences of discrimination against lesbian, gay, bisexual, transgender, and queer (LGBTQ) adults in the United States, which broadly contribute to poor health outcomes. Data Source and Study Design Data came from a national, probability‐based telephone survey of US adults, including 489 LGBTQ adults (282 non‐Hispanic whites and 201 racial/ethnic minorities), conducted January‐April 2017. Methods We calculated the percentages of LGBTQ adults reporting experiences of discrimination in health care and several other domains related to their sexual orientation and, for transgender adults, gender identity. We report these results overall, by race/ethnicity, and among transgender adults only. We used multivariable models to estimate adjusted odds of discrimination between racial/ethnic minority and white LGBTQ respondents. Principal Findings Experiences of interpersonal discrimination were common for LGBTQ adults, including slurs (57 percent), microaggressions (53 percent), sexual harassment (51 percent), violence (51 percent), and harassment regarding bathroom use (34 percent). More than one in six LGBTQ adults also reported avoiding health care due to anticipated discrimination (18 percent), including 22 percent of transgender adults, while 16 percent of LGBTQ adults reported discrimination in health care encounters. LGBTQ racial/ethnic minorities had statistically significantly higher odds than whites in reporting discrimination based on their LGBTQ identity when applying for jobs, when trying to vote or participate in politics, and interacting with the legal system Conclusions Discrimination is widely experienced by LGBTQ adults across health care and other domains, especially among racial/ethnic minorities. Policy and programmatic efforts are needed to reduce these negative experiences and their health impact on sexual and/or gender minority adults, particularly those who experience compounded forms of discrimination.